Organizational Commitment Antecedent and Its Effect on Managerial Performance in Public Sector Budgeting - Hayat, Atma (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2017)
Regional autonomy is intended to improve public services and local government's performance including the managerial performance in public sector budgeting. This study aims to obtain empirical evidence on the effects of antecedent variable in public sector budgeting in local government within organizational commitment and public sector managerial performance. This study employs positivist paradigm with quantitative approach. This is an explanatory study with the population of public sector managers scattered in 343 regional work units (SKPD) of South Kalimantan district and municipal government. This study uses samples of 217 public sector managers with analysis unit of public sector manager and technique of multistage random sampling. Decentralization and participation in budgeting significantly affect organizational commitment and managerial performance directly. Distributive justice in budgeting significantly affects organizational commitment yet has no significant effect on managerial performance, while organizational commitment significantly affects managerial performance. Furthermore, indirectly, organizational commitment can partially mediate the effects of decentralization on managerial performance as well as the effects of participation on managerial performance. While organizational commitment can fully mediate the effects of distributive justice on managerial performance. The results of overall study showed that participation in budgeting is the central variable in shaping organizational commitment, while the organizational commitment turns out to be the most dominant variable affecting managerial performance and becomes the bridge of managerial performance achievement when distributive justice has no significant effect on managerial performance.